Effects of Distributed Generation on Carbon Emission Reduction of Distribution Network - Wu, Di; Su, Jun; Chen, Zhengyu; Liu, Hanhan (Distributed Generation & Alternative Energy Journal, 2023)
Increasing renewable energy integration in power systems is an important way of decarbonising carbon emissions. Recently, the ever-increasing deployment of distributed generation (DG) is considered effective in reducing carbon emissions and power loss, such as wind, photovoltaic (PV), and combined heat and power generation (CHP) on the demand side. Thus, the evaluation of carbon emission flow (CEF) will be a crucial factor for distribution network planning with the integration of DGs, which may act as a supplemented indicator in addition to traditional power flow study. In the planning stage, it is paramount to ensure that decarbonisation process of the power distribution system is in line with environmental and technical targets. Thus, the paper proposes a modelling strategy to combine the power flow and carbon emission flow. It aims to analyse and calculate the CEF based on the power-flow study. The novel model satisfies the power flow and CEF balance and can be directly used to evaluate the decarbonization of power system. The results of this study can help relevant energy decision-makers to do appropriate renewable energy generation planning and guide the power system to achieve carbon neutrality.